PEMBANGUNAN SISTEM INFORMASI MONITORING KARYAWAN PADA BAGIAN LOGISTIK DI PT. MOWILEX INDONESIA. - Purnama, Deden; Purwanto, Purwanto; Herdiyanto, Herdiyanto (Universitas Lancang Kuning, 2023)
Mowilex Indonesia is a company engaged in manufacturing with more than 1000 employees. In managing employee data, this company does not yet have an integrated information system so that data management for employee activities has not been effective and efficient. Therefore, an information system is needed that can monitor all employee activities ranging from attendance, leave, mutation, promotion and other activities. With this system, companies can monitor employee activities easily and quickly, especially in making reports. The objectives of this study are 1) to create employee monitoring information system, 2) to provide convenience in making monitoring performance reports for management needs. This research uses waterfall development methods and Unified Modeling Language (UML) modeling as system design methods, while its implementation uses the PHP programming language with the help of sublime text and MYSQL databases with the help of navicat.